Extract of Plantago asiatica L. Seeds Ameliorates Hypertension in Spontaneously Hypertensive Rats by Inhibition of Angiotensin Converting Enzyme - Tong, Ren-Chao; Qi, Meng; Yang, Qi-Ming; Li, Peng-Fei; Wang, Dan-Dan; Lan, Ji-Ping; Wang, Zheng-Tao; Yang, Li (Frontiers in Pharmacology, 2019)
Plantago asiatica L. seeds is a common folk medicine with a long history of medical use in China because of its antipyretic, diuretic, and expectorant properties. It has been applied to treat hypertension clinically due to its diuresis, however, its efficacy and mechanisms on antihypertension has not been reported yet to our knowledge. In this study, we investigated the antihypertensive effect and underlying mechanisms of Plantago asiatica L. seeds extract (PASE) in spontaneously hypertensive rat (SHR). Male SHRs were treated with 2.5 mg/kg of fosinopril (FOS) and 400 mg/kg of PASE orally per day for once or 12 weeks. SHR or Wistar-Kyoto rats (WKY) receiving vehicle (distilled water) was used as control. The results demonstrated systolic, diastolic and mean blood pressures (SBP, DBP and MBP) were significantly lowered after single and long-term intragastric administration of PASE. The cardiac and aortic index and collagen accumulation were improved in the PASE group compared with the SHRs group. Meanwhile, PASE treatment remarkably reduced urine total protein, the ratio of serum urea nitrogen to serum creatinine and increased serum potassium. The levels of serum angiotensin I (Ang I), angiotensin II (Ang II), the ratio of Ang II to Ang I and aldosterone (ALD) were lowered after treatment of PASE. Besides, PASE and its major active constituents of phenylethanoid glycosides, including isoacteoside, plantamajoside and acteoside, were found to effectively inhibit angiotensin-converting enzyme (ACE) activation in vitro. These findings suggest that PASE has the antihypertensive effect that may involve a mechanism of ACE inhibition and simultaneously protect organ damage against hypertension.